Walk-in clinics: implications for family practice. - Rizos, J (1990)
To understand better the reasons for the growth in popularity of walk-in clinics in Canada we surveyed 321 patients with a regular physician in Toronto who attended a walk-in clinic in the same city over a 16-day period in February 1988. They were asked their reason for attending the clinic, their perception of the urgency of their problem, their choices as alternatives to walk-in clinics and their satisfaction and concerns with the type of care received at the clinic. The three most common reasons for attending the clinic were convenient location (in 33% of the cases), inability to see their regular physician soon enough (in 16%) and no appointment needed (in 13%). Most (80%) of the patients felt that they needed medical attention within 24 hours after the onset of their problem. Most (83%) of the respondents would have sought medical attention at another walk-in clinic, from their regular physician or at an emergency department had the clinic been closed. Only 36% and 18% of the patients respectively responded that their regular physician worked evenings or weekends. Most of the visits to the clinic were outside regular weekday business hours. The level of satisfaction with the service received at the clinic was high. The extended hours and no-appointment philosophy of walk-in clinics, coupled with family physicians' reluctance to work evenings and weekends, have made such clinics an attractive option for patients with primary care problems that they believe require prompt attention.